Acute mental stress drives vascular inflammation and promotes plaque destabilization in mouse atherosclerosis. (19th July 2021) - Hinterdobler, Julia; Schott, , Simin; Jin, Hong; Meesmann, Almut; Steinsiek, Anna-Lena; Zimmermann, Anna-Sophia; Wobst, Jana; Müller, Philipp; Mauersberger, Carina; Vilne, Baiba; Baecklund, Alexandra; Chen, Chien-Sin; et al.
Abstract: Aims : Mental stress substantially contributes to the initiation and progression of human disease, including cardiovascular conditions. We aim to investigate the underlying mechanisms of these contributions since they remain largely unclear. Methods and results : Here, we show in humans and mice that leucocytes deplete rapidly from the blood after a single episode of acute mental stress. Using cell-tracking experiments in animal models of acute mental stress, we found that stress exposure leads to prompt uptake of inflammatory leucocytes from the blood to distinct tissues including heart, lung, skin, and, if present, atherosclerotic plaques. Mechanistically, we found that acute stress enhances leucocyte influx into mouse atherosclerotic plaques by modulating endothelial cells. Specifically, acute stress increases adhesion molecule expression and chemokine release through locally derived norepinephrine. Either chemical or surgical disruption of norepinephrine signalling diminished stress-induced leucocyte migration into mouse atherosclerotic plaques. Conclusion : Our data show that acute mental stress rapidly amplifies inflammatory leucocyte expansion inside mouse atherosclerotic lesions and promotes plaque vulnerability. Graphical Abstract: